Pemanfaatan lemak fleshing tersulfonasi untuk peminyakan pada proses penyamakan kulit - Sutyasmi, Sri (Majalah Kulit, Karet, dan Plastik, 2009)
The objective of this research was to produce sulfonated oil of fleshing grease and to use for fat liquoring process in leather tanning industries. Fleshing wastes were collected from Yogyakarta. The extract was obtained from fleshing waste by boiling at 100o C for 15 minute 400 â 450 g of extract contained 99.96% of fat were obtained from 5 kg of fleshing. The extract then was sulfonated to increase solubility in water and more reactive with the fiber of processed skin. The sulfonated extract was then analyzed to determine content, iodine value, acid value and saponification value. The result of analysis showed that fat/grease content 158.48. While fat content of goat skin fleshing was 30.27%, iodine value 92.30, acid value 23.74and saponification value 157.03. The quantity parameters are able to meet requirement for leather tanning. Sulfonated extract was then used for fat liquoring process of goat skin with the variation of concentration 4,5 and 6% respectively. Control was made by using 5% synthetic oil. The result of crust testing in this research showed that all of quality parameters meet the document of SNI 06-3536-1994 about goat/sheep crust leather.Â Key words : leather, tanning, fleshing, sulfonation greasing.Â Â ABSTRAKÂ Tujuan penelitian adalah mendapatkan minyak limbah flesing tersulfonasi, digunakan untuk peminyakan industri penyamakan kulit. Limbah fleshing untuk peneltiian diambil dari industri penyamakan kulit Yogyakarta. Pengambilan lemak limbah fleshing dengan cara perebusan pada suhu (100o C selama 15 menit). Perebusan 5 kg limbah fleshing diperoleh ekstrak 400 â 450 g dengan kadar lemak 99,96%. Selanjutnya lemak disulfonasi agar mudah larut dalam air, dan mudah bereaksi dengan kulit. Lemak yang telah disulfonasi diuji kadar lemak/minyak, bilangan yod, bilangan asam dan bilangan penyabunan. Hasil uji lemak sulfonasi menunjukkan bahwa lemak fleshing kulit sapi mempunyai kadar lemak/minyak 40,13%, bilangan yod 88, bilangan asam 31,52 dan bilangan penyabunan 158,48. Sementara lemak/minyak 30,27%, bilangan yod 92,3, bilangan asam 33,74 dan bilangan penyabunan 157,03. Parameter mutu lemak fleshing kulit sapi maupun kulit kambing memenuhi persyaratan sebagai peminyakan dalam proses penyamakan kulit. Lemak sulfonasi yang dihasilkan untuk peminyakan penyamakan kulit krus kambing dengan variasi berturut-turut : 4,5 dan 6%. Sebagai kontrol digunakan minyak sintetis 5%. Hasil uji kulit krus kambing sesuai dengan ketentuan yang dimuat SNI: 06 â 3536 â 1994, tentang kulit krus domba/kambing.Â Kata kunci: kulit, penyamakan, fleshing, lemak tersulfonasi.